LEXICALLY NARRATIVE ANALYSIS OF ‘KEEP YOUR FRIENDS CLOSE’ FROM EPIC: THE MUSICAL IN EFL LEARNING - Neviana Ramadhini; Yohanes Gatot Sutapa Yuliana Yuliana (LPPM STBA Pontianak, 2026)
This study aimed to analyze the narrative and lexical aspects of Jorge Rivera-Herran's song